2012
DOI: 10.1089/vim.2011.0094
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Central Conserved Region of Respiratory Syncytial Virus (RSV) G Protein Block RSV G Protein CX3C-CX3CR1 Binding and Cross-Neutralize RSV A and B Strains

Abstract: Respiratory syncytial virus (RSV) is a primary cause of severe lower respiratory tract disease in infants, young children, and the elderly worldwide, and despite decades of effort, there remains no safe and effective vaccine. RSV modifies the host immune response during infection by CX3C chemokine mimicry adversely affecting pulmonary leukocyte chemotaxis and CX3CR1+ RSV-specific T-cell responses. In this study we investigated whether immunization of mice with RSV G protein polypeptides from strain A2 could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 69 publications
3
56
0
Order By: Relevance
“…This synthetic peptide induced a greater neutralizing antibody response to RSV than did the peptides flanking it (Choi et al 2012). These antibodies also inhibited G protein binding to CX3CR1 and reduced the effect of the G protein on lymphocyte migration.…”
Section: Vaccine Implicationsmentioning
confidence: 99%
“…This synthetic peptide induced a greater neutralizing antibody response to RSV than did the peptides flanking it (Choi et al 2012). These antibodies also inhibited G protein binding to CX3CR1 and reduced the effect of the G protein on lymphocyte migration.…”
Section: Vaccine Implicationsmentioning
confidence: 99%
“…Another advantage of the G protein as a vaccine candidate is the presence of neutralizing epitopes that are comparatively independent of protein structure. Several approaches, including subunit-, nanoparticle-, peptide-, and bacterial-based vaccines have been tried, and an mAb against G protein has been demonstrated to inhibit the virus infection in animal models (55)(56)(57)(58)(59)(60). However, the association of the G protein with VED indicates the need for caution during its development as an RSV vaccine (26).…”
mentioning
confidence: 99%
“…Tripp, Anderson, and colleagues have shown that antibodies specific to this CX3C sequence motif block the binding of G protein to the CX3C receptor, and that immunization with a peptide encoding the CX3C motif protected mice from RSV challenge and decreased pulmonary inflammation (Zhang et al 2010). These studies have recently been extended showing some cross reaction of antibodies raised to this region to RSV-B G protein in mice (Choi et al 2012) indicating that inclusion of this region of the G protein in vaccine candidates may increase protective responses to both RSV A and B.…”
Section: Peptide Vaccine Candidatesmentioning
confidence: 94%